THE KINETICS OF VESICLES SWELLING IN PRESENCE OF TRANSMEMBRANE DIFFERENCE OF POTENTIALS - Arakelyan, V. B.; Aramyan, K. S.; Arustamyan, V. M.; Gevorgyan, H. K.; Karamyan, K. K.; Vardanyan, V. I.; Potikyan, G. G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
It is shown, that the transmembrane difference of potentials applied to vesicles causes the decrease of the swelling time. Vesicle swelling time exponentially decreases with the increase of the potential. The swelling time of vesicle is greatly increased with the increase of work for the porous perimeter unit formation.